Protocol for the DisCoVeRy trial: multicentre, adaptive, randomised trial of the safety and efficacy of treatments for COVID-19 in hospitalised adults - Florence Ader; Jean-François Timsit; Yazdan Yazdanpanah; François-Xavier Lescure; Laetitia Moinot; Christelle Delmas; Hélène Espérou; Laurent Abel; Benjamin Leveau; Vinca Icard; Toni Alfaiate; Linda Wittkop; et al. (BMJ Open)
Introduction To find effective and safe treatments for COVID-19, the WHO recommended to systemically evaluate experimental therapeutics in collaborative randomised clinical trials. As COVID-19 was spreading in Europe, the French national institute for Health and Medical Research (Inserm) established a transdisciplinary team to develop a multi-arm randomised controlled trial named DisCoVeRy. The objective of the trial is to evaluate the clinical efficacy and safety of different investigational re-purposed therapeutics relative to Standard of Care (SoC) in patients hospitalised with COVID-19.Methods and analysis DisCoVeRy is a phase III, open-label, adaptive, controlled, multicentre clinical trial in which hospitalised patients with COVID-19 in need of oxygen therapy are randomised between five arms: (1) a control group managed with SoC and four therapeutic arms with re-purposed antiviral agents: (2) remdesivir + SoC, (3) lopinavir/ritonavir + SoC, (4) lopinavir/ritonavir associated with interferon (IFN)-β−1a + SoC and (5) hydroxychloroquine + SoC. The primary endpoint is the clinical status at Day 15 on the 7-point ordinal scale of the WHO Master Protocol (V.3.0, 3 March 2020). This trial involves patients hospitalised in conventional departments or intensive care units both from academic or non-academic hospitals throughout Europe. A sample size of 3100 patients (620 patients per arm) is targeted. This trial has begun on 22 March 2020. Since 5 April 2020, DisCoVeRy has been an add-on trial of the Solidarity consortium of trials conducted by the WHO in Europe and worldwide. On 8 June 2020, 754 patients have been included.Ethics and dissemination Inserm is the sponsor of DisCoVeRy. Ethical approval has been obtained from the institutional review board on 13 March 2020 (20.03.06.51744) and from the French National Agency for Medicines and Health Products (ANSM) on 9 March 2020. Results will be submitted for publication in peer-reviewed journals.Trial registration number NCT04315948 Eudra-CT 2020-000936-23.